2011
DOI: 10.1088/0031-9155/56/20/005
|View full text |Cite
|
Sign up to set email alerts
|

Fast generation of 4D PET-MR data from real dynamic MR acquisitions

Abstract: We have implemented and evaluated a framework for simulating simultaneous dynamic PET-MR data using the anatomic and dynamic information from real MR acquisitions. PET radiotracer distribution is simulated by assigning typical FDG uptake values to segmented MR images with manually inserted additional virtual lesions. PET projection data and images are simulated using analytic forward projections (including attenuation and Poisson statistics) implemented within the image reconstruction package STIR. PET image r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 30 publications
0
60
0
Order By: Relevance
“…A fast analytic PET scanner simulation toolkit was then used to generate realistic dynamic projection data for the ECAT EXACT3D PET tomograph, following the method described in Tsoumpas et al 30,31 This simulation is based on the Software for Tomographic Image Reconstruction Release 2 (STIR) package, 32 derived from the concept first described by Ma et al 33,34 A recent study using this approach has shown that the most important cause of bias in the accuracy of kinetic parameters was PVEs. 35 Attenuation coefficient projection data were derived using the measured transmission data.…”
Section: Simulation Of Partial Volume Effectsmentioning
confidence: 99%
“…A fast analytic PET scanner simulation toolkit was then used to generate realistic dynamic projection data for the ECAT EXACT3D PET tomograph, following the method described in Tsoumpas et al 30,31 This simulation is based on the Software for Tomographic Image Reconstruction Release 2 (STIR) package, 32 derived from the concept first described by Ma et al 33,34 A recent study using this approach has shown that the most important cause of bias in the accuracy of kinetic parameters was PVEs. 35 Attenuation coefficient projection data were derived using the measured transmission data.…”
Section: Simulation Of Partial Volume Effectsmentioning
confidence: 99%
“…To simulate different types of realistic motion during a dynamic scan, the fast analytic simulation toolkit (FAST) is used [15]. A dynamic 4D MRI scan, providing uniform temporal sampling over consecutive respiratory cycles during the dynamic scan, is used to generate the motion fields.…”
Section: D Phantom Using Mr-derived Motion Fieldsmentioning
confidence: 99%
“…From the difference image between the 2 UTE images, a number of regions of interest were segmented (soft tissue, cortical bones, liver and lungs) and used to construct the anatomical phantom. The myocardium, heart ventricles and large vessels were also segmented using a different ECG triggered balanced B-TFE MRI scan during free breathing (TR/TE 4.7 ms/2.36 ms, TFE factor 26, o ) [15,31]. The scan was subsequently respiratory gated again to the end-exhale position using a virtual navigator.…”
Section: D Anatomical Phantommentioning
confidence: 99%
See 2 more Smart Citations